Weed Management in Alfalfa -- 2005 - Jason A. Ferrell (EDIS)
This document is SS-AGR-229, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published January 2005.